Fruit Tree Farmers' Knowledge of Production and Marketing in the Al-Marj Plain Region of the Green Mountain - Libya - Dr. Samira Ibrahim Ali,; Salah Osman Mahmoud, (Journal of Scientific and Human Dimensions, 2026)
This study aimed to identify the knowledge levels and attitudes of fruit tree farmers in the Sahel Al-Marj region and determine the factors influencing them. The specific objectives were to: describe the characteristics of the respondents; determine their technical, marketing, and administrative knowledge levels; analyze the correlation between knowledge levels and independent variables (age, educational level, farm size, years of experience in agriculture, and types of fruit trees planted); identify the variables most responsible for the variance in knowledge levels (relative effect); and identify the production and marketing obstacles facing farmers in the region.The study employed a descriptive-analytical approach, conducted on a random sample of 95 farmers. Data were collected through structured personal interviews using a pre-designed questionnaire. The data were processed and analyzed using the Statistical Package for the Social Sciences (SPSS v.26), utilizing frequencies, percentages, mean scores, Pearson Correlation, and Multiple Regression analysis
Keywords: Agricultural Knowledge; Fruit Farmers; Agricultural Production; Agricultural Marketing; Sahel Al-Marj; Al-Jabal Al-Akhdar